First, let's solve for the tangent line at x = 2.
y = ln(3x).
We can solve this in two ways. I'll show you the second way later.
y' = 1/(3x) [3] = 3/(3x) = 1/x
Therefore, we obtain our slope m when x = 4. That is
m = 1/4
When x = 4, y = ln(3*4) = ln(12).
We now use the slope formula with (4, ln(12)) and (x, y).
(y2 - y1) / (x2 - x1) = m
[y - ln(12)] / [x - 4] = 1/4. Cross multiplying,
4[y - ln(12)] = x - 4. Dividing both sides by 4, we have
y - ln(12) = (1/4)x - 1. Adding ln(12) both sides,
y = (1/4)x - 1 + ln(12)
That is the equation of our line. To determine where this crosses the x-axis, we find the x-intercept by making y = 0.
0 = (1/4)x - 1 + ln(12)
1 - ln(12) = (1/4)x, and then multiplying both sides by 4 gives
4 - 4ln(12) = x
Therefore, the tangent value to y = ln(3x) at x = 2 crosses the x-axis at x = 4 - 4ln(12).
****
The second method to solve for the derivative of y = ln(3x) is as follows.
y = ln(3x). Use the log property of addition.
y = ln(3) + ln(x)
NOW, when you take the derivative of both sides, ln(3) is a constant, so
y' = 1/x.
Just an FYI.
2007-01-07 16:05:43
·
answer #1
·
answered by Puggy 7
·
0⤊
1⤋
First find the slope of the tangent line by taking the derivative of the curve.
y = ln 3x
e^y = e^(ln 3x) = 3x
(e^y)(dy/dx) = 3
dy/dx = 3/e^y = 3/(3x) = 1/x
at x = 2
dy/dx = 1/x = 1/2
Plugging in
y = ln 3x = ln (3*2) = ln 6
The equation of the tangent line is:
y - ln 6 = (1/2)(x - 2) = x/2 - 1
y = x/2 - 1 + ln 6
This crosses the x axis at y = 0
x/2 - 1 + ln 6 = 0
x/2 = 1 - ln 6
x = 2(1 - ln 6)
The answer is 2(1 - ln 6) â -1.5835189
2007-01-08 00:16:28
·
answer #2
·
answered by Northstar 7
·
0⤊
0⤋
4
2007-01-07 23:59:36
·
answer #3
·
answered by robyn 4
·
0⤊
0⤋
Simply take the derivative of the function to be able to find the slipe of the tangent line at a point
dy/dx=1/x
x=2 so the slope is .5
ln(6)=.5x+b
y=.5x+ln6-1
put 0 in for y and get 1-ln6=.5x
then solve
~-1.5835
2007-01-08 00:04:32
·
answer #4
·
answered by Anonymous
·
1⤊
0⤋
y = ln(3x)
dy/dx = 3/3x
sub x=2 into 3/3x:
dy/dx=1/2
sub.x=2 into y:
y=ln6
Eqn of tangent: (y-ln6)/(x-2)=1/2
2(y-ln6)=x-2
2y-ln36=x-2
2y=x-2+ln36
x=2y+2-ln36
When the line crosses the x-axis,y=0
x=2-ln36
x=-1.583518938
2007-01-08 00:03:23
·
answer #5
·
answered by A 150 Days Of Flood 4
·
0⤊
0⤋
y' = 1/x = 1/2
x = 2, y = ln 6
y - ln 6 = (1/2)(x-2)
If y = 0, x = 2-2ln 6
2007-01-08 00:02:21
·
answer #6
·
answered by sahsjing 7
·
0⤊
0⤋